GITR blockade facilitates T-reg mediated allograft survival - Sonawane, Samsher B. (2009)
BACKGROUND: Many models of transplant tolerance have been found to depend upon the induction of regulatory T cells (T-regs). Innate immune signals are known to down-regulate T-regs thereby augmenting immunity by abrogating regulatory T cell function. Such signals may also provide a barrier to transplantation tolerance mediated by T-regs. A number of cell surface molecules expressed by T-regs have been found to inhibit T-reg activity, the best characterized of which is the glucocorticoid-induced TNF receptor-related protein (GITR). METHODS: Using an adoptive transfer model of allograft rejection we can study the effects of inflammation and antigen-specific T-regs on graft survival. Inflammation resulting from the transplant procedure counter-regulates the suppressor activity of T-regs. To assess whether T-reg activity could be enhanced by blocking GITR signaling we compared the capacity of T-regs to prolong the survival of grafts in the presence or absence of AITRL-Fc, a novel construct that binds GITR. RESULTS: We report that interruption of GITR-GITRL binding by AITRL-Fc resulted in long-term T-reg-dependent acceptance of skin grafts in the setting of innate immune signals that otherwise interfere with T-reg activity. CONCLUSIONS: Inflammation and other innate immune signals may activate antigen presenting cells (APC) to upregulate GITRL. GITR-GITRL interaction is one pathway by which APCs may enhance the adaptive response to foreign antigen by counter-regulating T-regs and by costimulating effector T cells. By blocking this interaction with AITRL-Fc, one can sustain the benefit conferred by graft-protective T-regs.